Relationship of job level, burnout to job satisfaction and task performance in functional officers managing goods and services procurement in government institutions - Sumirat, Yuyun; Indradewa, Rhian (Jurnal Ekonomi dan Bisnis, 2023)
Emotional exhaustion, frustration or emotional or what is called burnout is the cause of bad work attitudes, unfocused concentration, and negative assessment of employees, in the world of work there are many things that affect a worker in achieving job satisfaction, factors that cause leaders and workers itself is not satisfied with the results of the work that has been completed due to fatigue, emotions, frustration. In this study, researchers used a sample of 166 employees of the Goods and Services Procurement Unit with a functional position as Goods/Services Procurement Manager for the State Civil Service of the Republic of Indonesia. Our study found that job level has a positive relationship with job satisfaction, and fatigue has a positive relationship with job level, job satisfaction, and task performance. While the level of work has no significant effect on employee performance. The findings of this study provide useful information for organizational development practitioners and researchers in understanding job satisfaction of UKPBJ Functional officials as well as job performance in the UKPBJ work environment. These findings are useful for professionals to better understand the dynamics of fatigue in promoting job satisfaction and job performance of employees based on their job levels and psychological problems of workers in the State Civil Service in the Republic of Indonesia.